2010
DOI: 10.1186/1471-2164-11-659
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle gene expression in response to resistance exercise: sex specific regulation

Abstract: BackgroundThe molecular mechanisms underlying the sex differences in human muscle morphology and function remain to be elucidated. The sex differences in the skeletal muscle transcriptome in both the resting state and following anabolic stimuli, such as resistance exercise (RE), might provide insight to the contributors of sexual dimorphism of muscle phenotypes. We used microarrays to profile the transcriptome of the biceps brachii of young men and women who underwent an acute unilateral RE session following 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 56 publications
6
100
1
4
Order By: Relevance
“…Consistently, concomitantly with a reduction in PGC-1α mRNA, SA strongly repressed the expression and activity of several metabolic-related proteins in both WT and mTg mice. Microarray analysis of human skeletal muscle has also revealed that resistance exercise does not increase the expression of genes involved in oxidative metabolism (38,39). In fact, resistance-trained athletes exhibit the same (38) or lower relative peak oxygen consumption compared with untrained healthy people (40).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, concomitantly with a reduction in PGC-1α mRNA, SA strongly repressed the expression and activity of several metabolic-related proteins in both WT and mTg mice. Microarray analysis of human skeletal muscle has also revealed that resistance exercise does not increase the expression of genes involved in oxidative metabolism (38,39). In fact, resistance-trained athletes exhibit the same (38) or lower relative peak oxygen consumption compared with untrained healthy people (40).…”
Section: Discussionmentioning
confidence: 99%
“…Androgen treatment leads to increases in strength and lean muscle mass (Hartgens and Kuipers, 2004), and these effects may be linked to testosterone-mediated changes in gene expression (Montano et al, 2007;Labrie et al, 2005). Further, the effects of exercise on gene expression in muscle are sex-specific in humans (Liu et al, 2010), suggesting that different transcriptional pathways may underlie some of the sex differences in muscle. The pectoralis muscle, which is the major avian flight muscle, accounts for ~20% of the mass of an individual bird (Marden, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…O aumento na força parece estar associado aos padrões geneticamente determinados em homens e mulheres. Liu et al (2010) observaram que o gênero é fator determinante na regulação transcricional do bíceps braquial, pois o TR resulta em diferentes padrões de hipertrofia e força muscular. Mulheres tendem a apresentar rápida regeneração pós-treino e homens apresentam sinalização hipertrófica mais prolongada.…”
Section: Discussionunclassified